The comparison of maladaptive cognitive schemas and irrational beliefs among smoker and non-smoker students - Haniyeh Gholamzadeh; Mohammad Ghaderi Ramazi; Hamidreza Dehghan; Kouros Divsalar (Islamic Azad University, 2015)
Introduction: In the field of cognitive development, schemas construct is a pattern which is formed based on reality or experience to help people explain their experiences. Primary maladaptive schemas are some fixed and long-term topics and beliefs that are formed in childhood and to some extent are inefficient. These schemas are assumed as patterns for processing further experiences. Irrational beliefs are also a set of thoughts, beliefs, and notions in which there is compulsion, perfectionism and absolutism. They cause various emotional and behavioral disorders to appear. Addiction, on the whole, and particularly smoking addiction is one of the probable outcomes of cognitive distortions such as maladaptive cognitive schemas and irrational beliefs. Thus, the present study aimed to compare maladaptive cognitive schemas and irrational beliefs among smoker and non-smoker students. Methods: In this casual comparative research, a non-clinical sample of 80 female and male students was chosen by multi-level random sampling (40 smoking and 40 non-smoking students). In order to collect data, Young's Schemas Questionnaire - short form (YSQ-SF) and Jones irrational belief questionnaire (IBT) were used. For data analysis, multivariate analysis of variance (MANOVA) was applied. Results: The findings of the present study indicated that there were some meaningful differences between smoker and non-smoker students in both maladaptive cognitive schemas (emotional deprivation, abandonment/instability, dependence/incompetence, subjugation, entitlement/grandiosity, insufficient self-control/self-discipline) and irrational beliefs (demand for approval, emotional irresponsibility, hopelessness changes and perfectionism). Conclusion: There is no doubt that most of human's mental problems are due to primary maladaptive schemas and originate from irrational thoughts. Maladaptive cognitive schemas, particularly those which are basically formed as a result of unpleasant childhood experiences, cause the formation of false habits and behaviors. Thus, their treatment in smoking people is really important. Apart from maladaptive cognitive schemas, beliefs that are far from reality can pave the way for problems such as addiction by changing the attitude of people in interpreting events.